Superhydrophobic 3D‐Assembled Metallic Nanoparticles for Trace Chemical Enrichment in SERS Sensing. Issue 51 (19th October 2022) - Liu, Youhai; Zhang, Nan; Tua, Dylan; Zhu, Yingkun; Rada, Jacob; Yang, Wenhong; Song, Haomin; Thompson, Alexis C.; Collins, R. Lorraine; Gan, Qiaoqiang
Abstract: The performance of surface‐enhanced Raman spectroscopy (SERS) is determined by the interaction between highly diluted analytes and boosted localized electromagnetic fields in nanovolumes. Although superhydrophobic surfaces are developed for analyte enrichment, i.e., to concentrate and transfer analytes toward a specific position, it is still challenging to realize reproducible, uniform, and sensitive superhydrophobic SERS substrates over large scales, representing a major barrier for practical sensing applications. To overcome this challenge, a superhydrophobic SERS chip that combines 3D‐assembled gold nanoparticles on nanoporous substrates is proposed, for a strong localized field, with superhydrophobic surface treatment for analyte enrichment. Intriguingly, by concentrating droplets in the volume of 40 µL, the sensitivity of 1 nm is demonstrated using 1, 2‐bis(4‐pyridyl)‐ethylene molecules. In addition, this unique chip demonstrates a relative standard deviation (RSD) of 2.2% in chip‐to‐chip reproducibility for detection of fentanyl at 1 µg mL –1 concentration, revealing its potential for quantitative sensing of chemicals and drugs. Furthermore, the trace analysis of fentanyl and fentanyl‐heroin mixture in human saliva is realized after a simple pretreatment process. This superhydrophobic chip paves the way toward on‐site and real‐time drug sensing to tackle many societal issues like drug abuse and the opioid crisis. Abstract : A surface‐enhanced Raman spectroscopy chip is developed by combining 3D‐assembled gold nanoparticles on nanoporous substrates. With superhydrophobic surface treatment for analyte enrichment, it demonstrates a sensitive detection of fentanyl at the concentration of 1 µg mL –1 with a relative standard deviation of 2.2% in chip‐to‐chip reproducibility, revealing its potential for quantitative sensing of chemicals and drugs.